PENGUATAN JEJARING KOMUNITAS MELALUI TINDAKAN KOLABORATIF: Studi Pada Sepuluh Kampung Iklim di DKI Jakarta - Mahendro, Anggoro Yudo Mahendro (Saskara : Indonesian Journal of Society Studies, 2021)
This research is directed to strengthen the network among the drivers of the Climate Village program in ten RWs in DKI Jakarta. Using collaboration action research, this research uses focus group discussion techniques which are conducted twice in each community. During the FGD twice there was an increase in community network marked by the creation of an organizational structure and work program that had not been made so far. These two outcomes are certainly important for building relationships that are more equal to elements of the local government and also the private sector which tends to impose programs on the community.